Determinants of Consumer Purchase Decisions for Retro Gaming Consoles: Evidence from PlayStation 2 Products on Indonesian E- Commerce - Surianto; Renaldi Fitra Alrohman; Agung Stefanus Kembau; Kho Gerson Ralph Manuel (Jurnal Ragam Pengabdian, 2026)
The growth of e-commerce has significantly transformed consumer purchasing behavior, including in the gaming industry where retro gaming consoles such as the PlayStation 2 continue to attract consumer interest in online marketplaces. This study aims to examine the influence of product quality and promotion on consumer purchase decisions for PlayStation 2 products in the Tokopedia marketplace. A quantitative research approach was employed by collecting primary data through questionnaires distributed to 100 consumers who have purchased PlayStation 2 products on Tokopedia. The data were analyzed using multiple linear regression analysis with the assistance of IBM SPSS to evaluate the partial and simultaneous effects of product quality and promotion on purchase decisions. The findings indicate that product quality and promotion have a positive and significant effect on consumer purchase decisions, both individually and simultaneously. In conclusion, product quality plays a critical role in shaping consumer perceptions and trust toward the product, while promotional activities contribute to increasing consumer awareness and purchase intention in the digital marketplace environment. These results highlight the importance of maintaining product quality and implementing effective promotional strategies to enhance consumer purchasing decisions. This study contributes to the literature on consumer behavior in e-commerce, particularly within the context of retro gaming product markets.